Invasive Ductal Carcinoma in a Mammary Hamartoma: Case Report and Review of the Literature - Choi, Nami (The Korean Society of Radiology, 2010)
Mammary hamartomas are typically a benign condition and rarely develop into malignant lesions. Only 14 cases of carcinomas associated with a hamartoma have been documented in the literature. In this case report, we describe a case of invasive ductal carcinoma within a hamartoma in a 72-year-old woman. Mammography, ultrasonography, and magnetic resonance imaging showed the features of a typical hamartoma with a suspicious mass arising in it. This case illustrates the importance of identification of unusual findings in a typical mammary hamartoma on radiologic examinations.